KEMANUSIAAN, CINTA, DAN KEBAIKAN: STUDI DEKONSTRUKSI RAMAYANA OLEH RAJAGOPALACHARI - Puspitasari, Shochifah Diyah; Widyatwati, Ken; Suryadi, M (ELTIN Journal, 2024)
Ramayana is the famous story from India that have retold in many versions and translated into many languages. Ramayana has unique way in depicting characters between the protagonist and antagonist. In the story of Ramayana, Ravana as the antagonist character also has some good personality such as the way he treats Sita. According to the issues, the researcher tried to analyze binary oppositions in the story of Ramayana retold by C. Rajagopalachari by using the deconstruction theory of Jacques Derrida. This research is a qualitative descriptive research that focus on the antagonist character in this story namely Ravana. The data were taken from the quotations in the book to find out or explain the deconstruction analysis in the Ramayana retold by C. Rajagopalachari.  The result of this research showed that the binary oppositions are found in the antagonist character, Ravana. Thus, it can be concluded that Ravana as antagonist character actually has a character who brings humanity, love, and kindness.